Immunomodulatory potential of particular Trichinella spiralis muscle larvae excretory–secretory components. Issue 13 (December 2016) - Cvetkovic, J.; Sofronic-Milosavljevic, Lj.; Ilic, N.; Gnjatovic, M.; Nagano, I.; Gruden-Movsesijan, A.
Graphical abstract: Highlights: 7C2C5Ag and rTsp53 possess capacity to induce Trichinella spiralis -influenced semi-mature status of dendritic cells (DCs). Weak activation of both kinases (ERK, p38) in stimulated DCs proved to be sufficient for Th2 polarisation in vitro. 7C2C5Ag and rTsp53 may contribute to a Th2 shift, an observed immunomodulatory effect of Trichinella ES L1 products. Abstract: Excretory–secretory antigens of Trichinella spiralis muscle larvae can induce the semi-matured status of rat dendritic cells. This may at least partly be the consequence of transient activation of extracellular signal-regulated kinases 1/2 (ERK1/2). Here we investigated the potential of several components of excretory–secretory antigens (native fraction containing 45, 49 and 53 kDa proteins and recombinant Tsp53, representing one of the constituents of this fraction) to demonstrate previously observed effects of excretory–secretory antigens on dendritic cells in vitro, characterised by establishment of a particular phenotype (very low MHC II expression, moderate CD86 expression and significant ICAM-1 expression) and functional properties (low production of pro-inflammatory cytokine IL-12p70, and high production of IL-10 and TGF-β). Dendritic cells activated by these components were able to provoke proliferation of naïve T cells and their polarisation towards Th2 and anti-inflammatory responses. The investigated antigens had almost the same capacity to induce IL-4 and IL-10 production from T cells as excretory–secretory antigens, but failed to induce significant TGF-β synthesis. It could be concluded that the investigated excretory–secretory antigens components can largely reproduce the immunomodulatory effects of the complete excretory–secretory antigens and therefore may be considered as molecules important for creation of the anti-inflammatory milieu achieved by the parasite.